A Review and Bibliometric Analysis Regarding Strategy Repurchase Intention - Sutrisno, Sutrisno (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The concept of strategic repurchase intention refers to the strategies used by companies to influence customer intentions to make repeat purchases or maintain loyalty to their brands or products. The aim of this paper is to provide an extensive bibliometric literature review on repurchase intention strategies. Article search uses the Publishing or Perish (PoP) application with the Google Scholar database. There are 43 out of 200 articles found from the Google Scholar database from 2022 to 2023. Selected references are then managed using the reference management software, namely Mendeley. After managing the database, this research classifies and visualizes it using VOSviewer software. Overall, this review provides an appropriate reference point for further research on strategy repurchase intention.